Legal Analysis of Default in House Building Contract Agreement - Taufika Hidayati; Winta Hayati (International Journal of Science and Environment (IJSE), 2025)
Building contracting is an act in which one party gives work to another party as a contractor to complete a building. Obstacles in practice in the field often occur so that there is a discrepancy in the agreement that has been agreed between the parties. To protect the parties, a building contracting agreement is needed so that there is a binding between the two parties. If one party cannot fulfill the performance (default) according to the agreed agreement, then the party who does not receive the performance from the other party can file an objection or even a lawsuit in court if no peace is reached between the parties. A contracting agreement is a reciprocal agreement between rights and obligations, in which there is an agreement between one party, namely the contractor, who binds himself to carry out the work, while the other party who contracts, binds himself to pay a predetermined price. With research that uses a normative legal approach, this study aims to determine the legal consequences of default for contractors in a house building contracting agreement.